A Study on Relationship Between Causative Factors and Machinery Accidents in Malaysian Construction Project - Birabakaran, Divagar; Nagapan, Sasitharan (Recent Trends in Civil Engineering and Built Environment, 2021)
Construction industry is one of the riskiest industries in Malaysia. The working environment in this industry is quite challenging and unpredictable. The amount of machinery accidents increases annually in this industry. Thus, it vital to take serious measures to reduce machinery accidents. For minimizing the machinery accident, it is very important to identify the factors causing machinery accidents and mitigation measures for the factors. The questionnaire survey was used to collect data for this study. The questionnaire is distributed to all construction professionals who are experienced in the construction field. A total of 117 questionnaires were received from the construction professionals. Spearman Correlation analysis was used to establish a correlation between the causation factors and machinery accidents. Unsafe work site (r = 0.885), unsafe method (r = 0.811), human error (r = 0.876), and poor management (r = 0.845) are among the factors which have very strong level of correlation with machinery accidents, while unsafe equipment (r = 0.463) and inadequate training (r = 0.577) are factors obtained moderate level of correlation with machinery accidents. The most suitable mitigations to reduce the causation factors is determined using Mean Rank Score method. The three most suitable mitigations are determined are inspect wellbeing of equipment at workplace regularly (mean score = 4.84), provide manual guideline on how to use certain equipment (mean score = 4.78) and provide enough lighting during night jobs or enclosed areas (mean score = 4.67). The findings of this study can be a useful guide for practitioners in controlling machinery accidents in construction sites.